PENGARUH ROA, DER, CR, INFLASI DAN KURS TERHADAP RETURN SAHAM (STUDI KASUS INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2008-2012) - Meri Arisandi (Jurnal Dinamika Manajemen, 2014)
The objectives of this research to analyze the influence of ROA, DER, CR, inflation and exchange rate to stock return on Food and Baverage industry that listed on Indonesian Stock Exchange in the period of 2008-2012.The number of population is 19 companiesand eligablesample is 16 companies. Analyze technique that use to analyze data is multiple linier regression. Analyses result showed that the partial results of Return On Asset (ROA), inflation and exchange rate variables has significant influence to stock return in other hand DER and CR has insignificantinfluenced to stock return on Food and Baverage industry.Keywords : On Asset (ROA), Debt to Equity Ratio (DER), Current Ratio (CR), Inflation, exchange rate, stock Return